«ЕДИГЕ» ДӘСТАНЫНЫҢ СЫРТ ЕЛЛЕРДЕ ҮЙРЕНИЛИЎИ - Алламбергенова, Г.К.; Бекбергенова, Г.А. (FAN va JAMIYAT, 2022)
This article discusses the issues of studying the Karakalpak folk epic "Edige" abroad. Some questions of the translation are analyze of "Edige" by the German scientist Karl Reichel.